Association of shock index with short-term and long-term prognosis after ST-segment elevation myocardial infarction - Ndrepepa, Gjin; Cassese, Salvatore; Xhepa, Erion; Fusaro, Massimiliano; Laugwitz, Karl-Ludwig; Schunkert, Heribert; Kastrati, Adnan (Coronary Artery Disease, 2019)
Background The association of shock index with long-term mortality after ST-segment elevation myocardial infarction (STEMI) remains poorly investigated. We aimed to assess the association between shock index and eight-year mortality after STEMI. Methods The study included 1369 patients with STEMI undergoing primary percutaneous coronary intervention (PPCI). Patients were categorized into three groups: a group with shock index in the first tertile (shock index, 0.21 to 0.52; n = 458), a group with shock index in the second tertile (shock index > 0.52 to 0.67; n = 457) and a group with shock index in the third tertile (shock index > 0.67 to 2.80; n = 454). The primary outcome was eight-year mortality. Results In patients with shock index in the first to third tertiles, inhospital cardiogenic shock (n = 153) occurred in 3.5, 3.9 and 26.2% of patients, respectively [adjusted odds ratio = 1.54, 95% confidence interval (CI) 1.40 to 1.69, P < 0.001]; 30-day deaths (n = 122) occurred in 2.8, 5.5 and 18.5% of patients, respectively [adjusted hazard ratio = 1.06 (1.01-1.12); P = 0.024]; eight-year deaths (n = 300) occurred in 22.9, 21.6 and 36.1% of patients, respectively [adjusted hazard ratio = 1.06 (1.02-1.11); P = 0.007] with all risk estimates calculated per 0.1 unit increment in shock index values. From 30 days to 8 years, deaths (n = 178) occurred in 20.7, 17.0 and 21.5% of patients in the first to third shock index tertiles, respectively (the difference was nonsignificant for all intertertile comparisons). Conclusions In patients with STEMI, elevated shock index is associated with the risk of inhospital cardiogenic shock and mortality up to 8 years after PPCI. The long-term adverse prognosis was almost entirely driven by events within the first 30 days.
CRIS-Team Scopus Importer:2023-03-08
Keywords: cardiogenic shock; mortality; shock index; ST-segment elevation myocardial infarction